2003
DOI: 10.1097/01.asn.0000077407.90309.65
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C–Dependent Increase in Reactive Oxygen Species (ROS) Production in Vascular Tissues of Diabetes

Abstract: Abstract. Hyperglycemia seems to be an important causative factor in the development of micro-and macrovascular complications in patients with diabetes. Several hypotheses have been proposed to explain the adverse effects of hyperglycemia on vascular cells. Both protein kinase C (PKC) activation and oxidative stress theories have increasingly received attention in recent years. This article shows a PKC-dependent increase in oxidative stress in diabetic vascular tissues. High glucose level stimulated reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
293
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(325 citation statements)
references
References 54 publications
(46 reference statements)
21
293
0
4
Order By: Relevance
“…Therefore, our data showing that glucose treatment increased the production of ROS in epithelioid SMCs further support the involvement of the hexosamine pathway. These results are also consistent with data in the literature showing that an increase in ROS production concurs with PKC activation in response to glucose treatment [44].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our data showing that glucose treatment increased the production of ROS in epithelioid SMCs further support the involvement of the hexosamine pathway. These results are also consistent with data in the literature showing that an increase in ROS production concurs with PKC activation in response to glucose treatment [44].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with the earlier supposition that in diabetic arterial wall, PKC activation is higher via PLC-mediated production of diacylglycerol (DAG) that activates PKC (Inoguchi et al, 2003). In the present study, the inhibitory potency (pIC 50 ) of PLC inhibitor, U-73122, was taken as a measure of PLC-activation involved in the myogenic tone.…”
Section: Responses To Vasoconstrictor and Role Of Phospholipase Csupporting
confidence: 89%
“…The NADPH oxidase complex consists of the membrane-associated flavocytochrome b 558 protein, which is composed of gp91 phox and p22 phox , and the cytosolic components p47 phox , p67 phox and p40 phox [35]. It has been reported that the diacylglycerol-protein kinase C pathway is stimulated in the malformed embryos of diabetic mice [36] and that protein kinase C stimulates NADPH oxidase expression [37]. Thus, the data we present here suggest that an increase in NADPH oxidase expression and subsequent ROS production result in the elevation of iNOS expression in embryos of diabetic mice.…”
Section: Discussionmentioning
confidence: 99%